Effect of Re-Used Lignite and Mineral Wool Growing Mats on Plant Growth, Yield and Fruit Quality of Cucumber and Physical Parameters of Substrates in Hydroponic Cultivation - Radosław Łaźny; Małgorzata Mirgos; Jarosław L. Przybył; Jacek S. Nowak; Małgorzata Kunka; Janina Gajc-Wolska; Katarzyna Kowalczyk (Agronomy, 2021)
In hydroponic cultivation of vegetables with a solid substrate, mineral wool predominates. The pro-ecological policy and consumers’ expectations cause an increase in interest in organic substrates, which, when properly used, are less harmful to the environment. The aim of this study was to determine the effect of reusing lignite substrate in hydroponic cultivation on the growth, yield and quality of cucumber fruit and on the physical parameters of the substrate. The greenhouse cucumber cultivar ‘Mewa F1’ with semi-long fruits and smooth skin was used for the study. The plants were grown in the ‘Carbomat’ lignite substrate and ‘Grotop Master’ rockwool in two cycles. In cycle 1, new growing mats were used, while in cycle 2 the same growing mats as in cycle 1 were used again. In the hydroponic cultivation carried out on mineral wool and in the lignite substrate, both in the new and the reused substrate, the cucumber obtained mostly similar plant growth parameters and fruit color. Cucumber grown on the new mineral wool had a higher number and weight of fruits, which were characterized by a higher content of β-carotene and lutein compared to fruits from plants grown in the new lignite substrate. On the other hand, the reused lignite substrate resulted in higher cucumber yields and fruits with higher firmness and higher carotenoid content compared to cucumber grown on reused mineral wool. At the same time, the content of dry matter and sugar extract in fruits obtained from plants growing in the new and reused lignite substrate was higher compared to fruits grown in mineral wool. Both new and reused lignite substrate were characterized by very low plant-available water content. In contrast; the air and water holding capacity of lignite after cultivation did not change as much as that of mineral wool.